Highly efficient solar driven cogeneration of freshwater and electricity. Issue 4 (4th January 2023) - Xu, Yunfan; Dong, Suwei; Sheng, Yuhang; Liu, Cihui; Xing, Fangjian; Di, Yunsong; Gan, Zhixing
Abstract : The integration of solar steam generation (SSG) and hydrovoltaic effect provides an ideal strategy for solving the water and energy shortage crisis. Abstract : The integration of solar steam generation (SSG) and hydrovoltaic effect provides an ideal strategy for solving the water and energy shortage crisis. However, it is still a challenge to collect freshwater while producing electricity at high efficiency. Here, we report the development of a solar driven freshwater-electricity cogeneration (SFEG) device based on a porous hydrophilic graphene aerogel (HGA). Under 1 sun irradiation, the SFEG device in deionized (DI) water exhibited an evaporation rate of 2.17 kg m −2 h −1 and an output voltage of 0.49 V. Moreover, we reveal that the output voltage and short-circuit current increase first and then decrease as salinity increases. When the salinity is 3.5%, the output voltage reaches 0.87 V with a maximum output power density of 6.84 μW cm −2, while the evaporation rate maintains 2.01 kg m −2 h −1 . Both the performances of water evaporation and electricity generation are very competitive compared to the state-of-the-art levels. The outdoor experiment demonstrates that the SFEG device can effectively work under real solar irradiation with good durability, suggesting great potential in practical applications.